Localised erythema nodosum leprosum-A rare entity managed with thalidomide - Chandni Patel; Barbara De Barros; Stephen L. Walker (Wiley, 2024)
Abstract Leprosy is caused by Mycobacterium leprae. The condition primarily affects the skin and peripheral nerves. There are two types of leprosy reactions, Type 1 and Type 2 or erythema nodosum leprosum (ENL). ENL is a severe multi‐system, immune‐mediated complication of lepromatous leprosy. It is characterised by widespread painful cutaneous nodules, fever and peripheral oedema. This report discusses the unusual case of a 29‐year‐old woman who developed a localised form of ENL which required thalidomide to induce remission.